2008
DOI: 10.1111/j.1365-2214.2008.00845.x
|View full text |Cite
|
Sign up to set email alerts
|

Are adolescents chronically sleep‐deprived? An investigation of sleep habits of adolescents in the Southwest of Germany

Abstract: The main hypothesis that students sleep on average considerably less than the recommended 9 h during weekdays was confirmed. Bedtimes changed throughout the week with the latest on Friday and Saturday nights and the least sleep around midweek. There were no significant group differences regarding school type and environment (rural vs. urban). Interestingly, the majority reported only little daytime sleepiness and no impaired performance. Results regarding the consequences of chronic sleep deprivation in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
4
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 33 publications
(62 reference statements)
5
82
4
10
Order By: Relevance
“…Embora não se saiba, com precisão, qual a necessidade média tabela 2. Razões de prevalências (RP) utilizando-se como variável dependente 8 ou menos horas de sono nos dias com aula de sono na adolescência, muitos jovens necessitam mais de 9 horas de sono 25,26 .…”
Section: Tabela 1 Resultados Descritivos Das Variáveis Investigadasunclassified
“…Embora não se saiba, com precisão, qual a necessidade média tabela 2. Razões de prevalências (RP) utilizando-se como variável dependente 8 ou menos horas de sono nos dias com aula de sono na adolescência, muitos jovens necessitam mais de 9 horas de sono 25,26 .…”
Section: Tabela 1 Resultados Descritivos Das Variáveis Investigadasunclassified
“…Com exceção dos estudos de Saarenpää-Heikkilä et al (18) e de Thorleifsdottir et al (15) , todos os trabalhos apresentaram desenho transversal. Na Tabela 1 encontra-se a síntese dos principais estudos analisados (3,5,7,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) . As escalas de sonolência Epworth Sleepiness Scale e a School Sleep Habits Survey foram as mais utilizadas para análise da sonolência diurna excessiva.…”
Section: Estudos Sobre Sonolência Diurna Excessivaunclassified
“…No estudo de Loessl et al (28) menos de nove horas de sono foi um fator associado a altos níveis de sonolência diurna excessiva. Já para Joo et al (2) , um dos principais fatores associados foi a insuficiência de sono percebida, mas o tempo total de sono foi semelhante nos jovens com e sem sonolência diurna excessiva, o que indica uma ausência de proteção desse fator.…”
Section: 1 Sexounclassified
“…4,7,8,15,16 Comparisons with other countries show similar patterns of decreased sleep durations with increasing age among adolescents. For example, in Northern Taiwan, 5 Germany, 14 and India, 17 average sleep duration dropped to below 8 hours for high school-aged students. The most precipitous drop was reported in 2005 for more than 1400 South Korean adolescents, for whom the average duration of sleep was 4.9 hours.…”
Section: Epidemiologic Studies Of Sleeping Adolescentsmentioning
confidence: 99%
“…It is important to note that studies comparing selfreported sleep duration with objectively measured sleep amounts (ie, with actigraphy) suggest that self-reports of sleep often overestimate actual sleep duration, signifying that the problem of chronic sleep loss in adolescents may be even greater than the data indicate. 12 US-based 4,13 and international studies 5,6,14 revealed that as students get older, sleep durations decline. The National Sleep Foundation Sleep in America Poll 4 found that by the 12th grade, 75% of students self-reported sleep durations of less than 8 hours of sleep per night compared with 16% of sixth graders.…”
Section: Epidemiologic Studies Of Sleeping Adolescentsmentioning
confidence: 99%